A Pragmatic Analysis Impersonal Deixis in the book “Barzani and the Kurdish Liberation Movement" by President Masoud Barzani (Raparin Journal of Humanities (RJH), 2026)
Deictic expressions play an essential role in enhancing textual clarity and coherence. They enable the writer to conveying events accurately and clearly, and help the reader understand these events without ambiguity, and making it easier to follow their chronological and spatial sequence, highlights the role of those who carried them out the, and the distribution of roles to the characters involved. Additionally, they function as cohesive devices linking sentences and paragraphs, thereby contributing to a unified textual structure. This study focuses impersonal deixis in "Barzani and the Kurdish Liberation Movement" by President Masoud Barzani, aiming to explore its function in reference resolution and meaning construction.    the study adopts a descriptive-analytical method to examine the forms and functions of deictic elements within the text. Then the research analyzed the most important indicative signs and how they affect the expression of meanings and their usage in the text. This analysis reveals that the author strategically employed these expressions to strengthen discourse cohesion and establish semantic connectivity across textual segments.